Differences in Maturity, Morphological, and Fitness Attributes Between the Better- and Lower-Ranked Male and Female U-14 Portuguese Elite Regional Basketball Teams. Issue 3 (March 2020) - Ramos, Sérgio; Volossovitch, Anna; Ferreira, António P.; Barrigas, Carlos; Fragoso, Isabel; Massuça, Luís
Abstract : Abstract: Ramos, S, Volossovitch, A, Ferreira, AP, Barrigas, C, Fragoso, I, and Massuça, L. Differences in maturity, morphological and fitness attributes between the better- and lower-ranked male and female U-14 Portuguese elite regional basketball teams. J Strength Cond Res 34(3): 878–887, 2020—During a national championship, the anthropometric, physiological, and maturation attributes of 13–14-year-old players of regional selection basketball teams and their association with team's final classification were analyzed. Body parameters (body mass, height, skinfolds, and lengths) were measured and physiological capacities assessed by sprint (20 m), agility, jump, and upper-body strength tests. Chronological age, maturity offset (years from age at peak height velocity; YAPHV), and predicted age at peak height velocity were calculated. In both sexes, no significant differences were found for maturity. Anthropometric and physiological analysis indicated that male players from finalist's teams were significantly faster, were more agile, threw the medicine ball longer, and showed lower percentages of body fat than players from lower-ranked teams. Further, semifinalists were faster than lower-ranked players. In the same sense, female players from semifinalist teams demonstrated to be significantly faster, more agile, and threw the medicine ball longer than female players from lower-ranked teams. In addition, discriminant analysis showed that speed (in boys) and the combination of speed and upper limb strength (in girls) could successfully discriminate players with different performances in a championship. In conclusion, speed and upper limb strength appear to be the physical attributes associated with better team performance in youth basketball. Coaches should be aware of the relationship between the improvement of these physical attributes and the teaching-learning process of the basketball game.